The Evaluation of Conceptual Learning and Epistemological Beliefs on Physics Learning by Think-Pair-Share - Tolga Gok (Journal of Education in Science, Environment and Health)
The purpose of the research was to investigate the effects of think pair share (TPS) instructional strategy on students' conceptual learning and epistemological beliefs on physics and physics learning. The research was conducted with two groups. One of the groups was the experimental group (EG) and the other group was the control group (CG). 35 students in the experimental group were instructed with think pair share instructional strategy while 36 students in the control group were instructed with conventional, teacher-centered teaching. Data were collected using "Mechanics Baseline Test (MBT)" which is used to monitor the conceptual learning of the students, "Colorado Learning about Science Survey (CLASS)" which is used to search for the epistemological beliefs on physics and physics learning of the students and students' opinions about think pair share instructional strategy. The results of the research revealed that think pair share instructional strategy had more positive effect on students’ conceptual learning and epistemological beliefs on physics learning than conventional teacher-centered teaching. The students in the experimental group also changed their perspective on conceptual learning and found the instructional strategy enjoyable. Besides, some suggestions based on the findings were presented at the end of research.